Clinical comparative study of glasses-free 3D and 2D thoracoscopic surgery in minimally invasive esophagectomy - Wei, Rongqiang; Ding, Xinyu; Chen, Zihao; Xin, Ning; Liu, Chengdong; Fang, Yunhao; Xu, Zhifei; Huang, Kenan; Tang, Hua (Frontiers in Oncology, 2022)
Objective To investigate the safety and efficacy of glasses-free three-dimensional (3D) thoracoscopic surgery in minimally invasive esophagectomy (MIE). Methods The clinical data of 98 patients, including 81 men and 17 women aged 45–77 years, with esophageal squamous cell carcinoma who underwent minimally invasive thoracoscopic esophagectomy from January 2017 to December 2019 [3 years, with clinical follow-up time: 1 year~4 years (2017.01–2020.12)] were retrospectively analyzed. Patients were divided into two groups according to different surgical methods including a glasses-free 3D thoracoscopic group (G-3D group: 38 patients) and a two-dimesional (2D) thoracoscopic group (2D group: 60 patients). The clinical outcome of the two groups were compared. Results The operation time of the thoracoscopic part in the G-3D group was significantly shorter than that in the 2D group (P<0.05). The total number of lymph node dissection in the G-3D group was more than that in the 2D group (P<0.05). The thoracic indwelling time, postoperative hospital stay, severe pulmonary infection, arrhythmia, anastomotic leakage, chylothorax, and recurrent laryngeal nerve injury were not significantly different between the two groups (P>0.05). There was also no significant difference between the two groups on the progression-free survival (P>0.05). Conclusion Glasses-free 3D thoracoscopic surgery for esophageal cancer is a safe and effective surgical procedure. Compared with 2D thoracoscopic MIE, glasses-free 3D thoracoscopic MIE for esophageal cancer has higher safety, more lymph node dissection, and higher operation efficiency through the optimized surgical operations. We believe that glasses-free 3D thoracoscopy for MIE is worthy of clinical promotion.